2011
DOI: 10.1038/cdd.2011.159
|View full text |Cite
|
Sign up to set email alerts
|

The inflammasome: in memory of Dr. Jurg Tschopp

Abstract: A decade ago, Jurg Tschopp introduced the concept of the inflammasome. This exciting discovery of a macromolecular complex that senses 'danger' and initiates the inflammatory response contributed to a renaissance in the fields of innate immunity and cell death. Jurg led the biochemical characterization of the inflammasome complex and demonstrated that spontaneous hyperactivation of this interleukin (IL)-1b processing machinery is the molecular basis of a spectrum of hereditary periodic fever syndromes, caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 91 publications
2
44
0
2
Order By: Relevance
“…Consistent with a previous report that many microtubule-associated proteins, including EB1, were up-regulated during macrophage activation (60), our iTRAQ analysis identified EB1 and numerous other microtubule-associated proteins that may participate in inflammasome activation (supplemental Table 1). We also identified an association between the activated NLRP3 inflammasome and HSP90, which was previously reported to stabilize the NLRP3 inflammasome prior to activation (61). Thus, this protein appears to also play an important role in the pre-activated inflammasome.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with a previous report that many microtubule-associated proteins, including EB1, were up-regulated during macrophage activation (60), our iTRAQ analysis identified EB1 and numerous other microtubule-associated proteins that may participate in inflammasome activation (supplemental Table 1). We also identified an association between the activated NLRP3 inflammasome and HSP90, which was previously reported to stabilize the NLRP3 inflammasome prior to activation (61). Thus, this protein appears to also play an important role in the pre-activated inflammasome.…”
Section: Discussionmentioning
confidence: 62%
“…In fact, it has been recently reported that the membrane attack complex of complement pores triggers inflammasome activation in the cytosol [43]. Whether the potassium and calcium mobilization induced by perforin [44] is associated with inflammasome activation and pyroptosis [45,46], and eventually antiviral activity, is a topic that deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the so-called inflammasome complex in the cytoplasm of phagocytic cells occurs via engagement of TLRs leading to subsequent assembly of the NLRP3 (NLR-related protein 3)-containing inflammasome complex and activation of caspase-1 with processing and secretion of the pro-inflammatory cytokine, interleukin (IL)-1β [36]. NLRP3 is also activated in response to host-derived particulate matter precipitates such as uric acid and cholesterol crystals and studies in recent years have shown that exogenous structures including asbestos fibers and crystalline silica also activate the inflammasome [37][38][39][40].…”
Section: Inflammasome Activationmentioning
confidence: 99%